1978
DOI: 10.1042/cs0540561
|View full text |Cite
|
Sign up to set email alerts
|

Renal Prostaglandins in Renal Hypertensive Dogs

Abstract: 1. Hypertension produced in two-kidney Goldblatt dogs was accompanied by a transient fluid retention, reaching a maximum 4 days after clamping. 2. Prostaglandin E and F concentrations in venous blood from the intact kidney also rose transiently, showing a maximum by the fifth day. 3. The rise in prostaglandin release from the intact kidney may be related to the fluid retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1981
1981
1985
1985

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Prostaglandin determination. The ethanol-extracted material was further extracted with ethyl acetate and assayed for PGF-a, PGE or 6-oxo-PGF-la by radioimmunoassay (Dighe, Emslie, Henderson, Rutherford & Simon, 1975;Dighe, Smith, Ungar & Whelpdale, 1978;Dighe, Jones & Poyser, 1978). Details of the cross-reactivities of the antisera have been reported previously (Poyser & Scott, 1980;Lytton & Poyser, 1982).…”
Section: Methodsmentioning
confidence: 99%
“…Prostaglandin determination. The ethanol-extracted material was further extracted with ethyl acetate and assayed for PGF-a, PGE or 6-oxo-PGF-la by radioimmunoassay (Dighe, Emslie, Henderson, Rutherford & Simon, 1975;Dighe, Smith, Ungar & Whelpdale, 1978;Dighe, Jones & Poyser, 1978). Details of the cross-reactivities of the antisera have been reported previously (Poyser & Scott, 1980;Lytton & Poyser, 1982).…”
Section: Methodsmentioning
confidence: 99%
“…The finding that several experimental models of glomerular damage show certain common quantitative and qualitative alterations in AA metabolism suggests the importance of this modulatory pathway in glomerular pathophysiology (17)(18)(19). Glomerular production of TxB2 might be one of the factors responsible for the altered glomerular filtration rate in disease (8).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, sodium restriction increases renal production of PGE in the rabbit (Stahl, Attallah, Bloch & Lee, 1979). In a previous study from this laboratory on Goldblatt two-kidney hypertension in conscious dogs results suggested that there is an increase in the concentration of PGE in renal venous blood from the intact kidney after the early phase of hypertension associated with the spontaneous excretion of retained sodium and water (Dighe et al, 1978). Since in this study the accumulated salt and water was removed by dialysis, the failure of the concentration of PGE in renal venous blood to increase implies that the PGE released by the untouched kidney is involved in sodium excretion, and would be consistent with the suggestion that PGE produced within the kidney exerts a natriuretic action, and that its release from the intact kidney is triggered by the retention of sodium and water.…”
Section: Urinary Outputmentioning
confidence: 87%
“…Previous results from this laboratory of studies of Goldblatt two-kidney hypertensive dogs suggested that increased prostaglandin E (PGE) pro- duction by the untouched kidney several days after the partial occlusion of the contralateral renal artery mediated the excretion of salt and water that had been retained over the first 4 days (Dighe, Smith, Ungar & Whelpdale, 1978). In the present study, to test this hypothesis further, salt and water that accumulated during the 2 days after the partial occlusion of one renal artery was removed by haemodialysis.…”
Section: Introductionmentioning
confidence: 98%